Optionality as an indicator of language development - N.H. Sharypova, A.A. Bilyalova,; A.R. Valeeva, R.D. Shakirova, A.I. Islamova, (Opción, 2019)
In the paper by optionalitywe mean a speech modification functioning in the language, manifested in a peculiar deviation within the norm, which exists alongside with the codified literary obligatory variant in certain linguistic and extralinguistic conditions. The functional-dynamic method is one of the main methods we used in here. For the analysis of faculty, an attempt is made to use the studied parameters of such a linguistic phenomenon as variance. Thus, we suppose that the phenomenon of optionality is basically associated with the processes of changes in linguistic systems and is a factor in the dynamics of linguistic development.